IN MEMORY OF ARKADY VIKTOROVICH KRYAZHIMSKIY (1949–2014) - Sergei M. Aseev; Alexander G. Chentsov; Alexey A. Davydov; Nikolai L. Grigorenko; Vyacheslav I. Maksimov; Elena A. Rovenskaya; Alexander M. Tarasiev (Ural Mathematical Journal, 2016)
The article is devoted to the description of Academician Arkady Kryazhimskiy's life path. The facts of the scientific biography of Acad. Kryazhimskiy are presented with the emphasis on his outstanding contribution into the theory of dynamic inversion, the theory of differential games, and control theory. His personal talents in different spheres are also marked out.